A study on maintenance management at private hospital in Klang Valley / Siti Nurhakimah Ramle - Ramle, Siti Nurhakimah (2008)
There is growing need and demand for Private Hospital service in Malaysia. This can be seen from the amount of Private Hospital in Malaysia. The study focuses on maintenance management at Private Hospital in Klang Valley area. To complete this research, five numbers of Private Hospitals were selected as case studies. Maintenance in each private hospital was control by hospital maintenance department. Scope of work for maintenance at each hospital is totally covered by them but there is some of work which is need specialist will be outsourced to contractor. Aim of this dissertation is to study the maintenance management at Private hospital building and make some improvement to maintenance management system there. To achieve the aim of this study, five objectives have been set, to overview the nature of maintenance management, to understand and to know about maintenance management practice at private hospital in terms of maintenance organization, to study about maintenance programmed, to identify the problems faced during maintenance works and solution to the problems and to recommend anything related with maintenance management to management staff. This research focused on Private hospital building’s in Klang Valley. The methods that really assist in this dissertation is by using Primary data and secondary data were gathered from questionnaire, site visits, observation, interviews and technical publications such as books, articles, journal and internet. To analyze the questionnaire, it can be using the Microsoft Excel. Through the interview session, visual observation and questionnaire, it will define that the information or data was collected. There are some aspects in term of maintenance management practice at private hospital will be define such as the problem occurred for instance the lack of maintenance staff, the lack of maintenance budget, improper maintenance programmed, control and monitoring the maintenance staff and record system of maintenance work. It is hope that this dissertation would give clear perception to the reader on maintenance management concept and hope that this may be of direct assistance to the practical application of management of maintenance work.